2022
DOI: 10.1021/acsami.2c13543
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic Potential-Induced Co–N4 Active Centers in a 2D Conductive Metal–Organic Framework for High-Performance Lithium–Sulfur Batteries

Abstract: The use of single-atom catalysts is a promising approach to solve the issues of polysulfide shuttle and sluggish conversion chemistry in lithium−sulfur (Li−S) batteries. However, a single-atom catalyst usually contains a low content of active centers because more metal ions lead to generation of aggregation or the formation of nonatomic catalysts. Herein, a 2D conductive metal−organic framework [Co 3 (HITP) 2 ] with abundant and periodic Co−N 4 centers was decorated on carbon fiber paper as a functional interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…The CoSAC@CNTs present a notable surface area (S BET ) of 920.15 m 2 g −1 , surpassing the reported values of other Co-containing catalysts from previous studies. 58,59 As per computations based on the density functional theory (DFT) methodology, the material has an average pore size of 9.7 nm and an overall pore volume of 1.4 cm 3 g −1 . The process of pyrolysis plays a role in controlling the specific surface area and porosity of substances.…”
Section: Resultsmentioning
confidence: 99%
“…The CoSAC@CNTs present a notable surface area (S BET ) of 920.15 m 2 g −1 , surpassing the reported values of other Co-containing catalysts from previous studies. 58,59 As per computations based on the density functional theory (DFT) methodology, the material has an average pore size of 9.7 nm and an overall pore volume of 1.4 cm 3 g −1 . The process of pyrolysis plays a role in controlling the specific surface area and porosity of substances.…”
Section: Resultsmentioning
confidence: 99%
“…It indicated that the space double layer could not induce obvious current signals under these testing conditions. [49] Then, using the electrolyte with 0. [50,51] Also, the peak currents of Ni 12 P 5 -Ni 2 P electrodes are higher than those of Ni 12 P 5 and Ni 2 P electrodes, demonstrating the enhanced Li 2 S 6 conversion by the interfaces in Ni 12 P 5 -Ni 2 P.…”
Section: Resultsmentioning
confidence: 99%
“…9b). 203 Permeation test results of the functional separator showed CoHP could effectively suppress the shuttle of LiPS through chemical bonding. More importantly, the highly conductive CoHP provided rapid electron transfer to activate efficient single-atom active sites at Co-N 4 , which significantly improved catalytic performance.…”
Section: Functional Sasc Interlayers For Li-s Batteriesmentioning
confidence: 99%